A DIGITAL TOURISM MAP TO GUIDE THE FEATURED TOURIST LOCATIONS IN THE BENDOSARI-PUJON TOURISM VILLAGE - Nursyifani, Cahyaning Umul Chasanah; Aprillia Putri, Safitri (SEEIJ (Social Economics and Ecology International Journal), 2024)
Each tourist village has its own set of attractions; that being said, Bendosari-Pujon Tourism Village offers its own beautiful. This village in Malang Regency provides dairy farming, milk processing, and plantation excursions. Additionally, one of the village famous sites, Grojokan Sewu Waterfall is really popular. Bendosari-Pujon Tourism Village is unique in that it converts cow dung into biogas. However, the wide terrain of Bendosari Village makes tourist sites difficult to reach without a car. This issue significantly lowers visitors' awareness of Bendosari Village's tourist attractions. Rapid technological growth has benefited humanity in numerous ways. Almost every productive-aged person utilizes a smartphone on a regular basis. This could help share information. Based on this rationale, the researchers employed descriptive, qualitative methodologies to find the best option. During data collection, researchers were able to restrict Bendosari Village's advertising needs and expand its tourism attractions thanks to technological advances. The research seek to identify the most effective digital channel for promoting key tourist destinations.